Study of the degree of defoliation of common oak (Quercus robur L.) in the conditions of the Main Botanical Garden named after N. V. Tsitsina RAS (Moscow) - Volkova Olga; KHotsialova Lidija (Hortus Botanicus)
When studying the harmful effects of chemical air pollutants of anthropogenic origin on forest ecosystems and, specifically, on woody plants, an important indicator is the state of the tree crown - the degree of defoliation. To determine the degree of air pollution in the Main Botanical Garden named after N. V. Tsitsin RAS (Moscow) over the course of several years determined the defoliation class of common oak (Quercus robur L.), as a tree species that is especially sensitive to the effects of air pollutants. During the observation period (2016 - 2023), defoliation in oak was practically absent or was insignificant, therefore, it can be concluded that the Main Botanical Garden lacks severe atmospheric air pollution.